A high-toughness impact-resistant and wear-resistant mortar and its preparation method and application

By using slag sulfaluminate cement and predispersed basalt fiber combined with water-based polyurethane emulsion, the impact resistance and durability of the mortar repair structure of the hydropower station flood discharge building structure is solved, and efficient compression, flexural and anti-resistance is achieved. Improve impact performance while reducing production costs.

CN118324480BActive Publication Date: 2025-01-10POWER CHINA KUNMING ENG CORP LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410435893.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-01-10
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

The repair mortar of existing hydropower station flood discharge building structures has shortcomings in impact resistance, flexural resistance and durability, especially the fiber dispersion difficulties, insufficient adhesion and alkali corrosion resistance of fiber toughening mortar.

Method used

Slag sulfaluminate cement is used as the basic material, combined with predispersed basalt chopped fibers and aqueous polyurethane emulsion, chemical bonds are formed through silane coupling agents, which improves the tensile flexural strength and impact resistance of the mortar, and is pretreated. The fiber improves its dispersion.

Benefits of technology

It significantly improves the compressive strength, flexural strength and impact resistance of the mortar, extends the service life, and reduces production costs, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118324480B_ABST
    Figure CN118324480B_ABST
Patent Text Reader

Abstract

The present invention provides a high-toughness impact-resistant and wear-resistant mortar and a preparation method and application thereof, belonging to the technical field of building repair materials. The high-toughness impact-resistant and wear-resistant mortar comprises the following raw materials by weight: 20 to 30 parts of slag sulphoaluminate cement, 55 to 65 parts of high-strength aggregate, 5 to 12 parts of pre-dispersed basalt chopped fibers, 3 to 6 parts of water-based polyurethane emulsion, 0.05 to 0.1 parts of silane coupling agents, and 0.02 to 0.08 parts of water reducers; wherein the pre-dispersed basalt chopped fibers comprise the following raw materials by weight: 15 to 25 parts of basalt short fibers and 75 to 85 parts of granulated blast furnace slag powder. The present invention also includes a preparation method of the high-toughness impact-resistant and wear-resistant mortar and its application in the preparation of flood discharge building repair materials for hydropower points. The high-toughness impact-resistant and wear-resistant mortar prepared by the present invention has good anti-scouring and wear resistance, flexural resistance and durability, and has promotion and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building repair materials, and specifically relates to a high-toughness impact-resistant and wear-resistant mortar and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of water conservancy and hydropower engineering construction in my country, a large number of large hydropower stations have been built and put into operation. Hydropower stations generate electricity by using high-speed water flow to drive turbine blades to generate electricity. During the power generation process, high-speed water flow containing sand and gravel will cause serious scouring and abrasion damage to the building structure. There are two mechanisms for the destructive action of high-speed water flow containing sand and gravel on concrete structures. One is the impact damage caused by cavitation. There are a large number of low-pressure air bubbles in the high-speed water flow. When they burst on the concrete surface, the micro-jets formed impact the material surface, causing cavitation damage; the other is that a large amount of sand and gravel contained in the water flow continuously scours the concrete surface, forming wear damage. That is, the damage to concrete is the result of the combined action of sediment wear and cavitation caused by the sand-carrying water flow on its surface. Due to the presence of a large number of solid particles in the sand-carrying water flow, and these solid particles have uneven surfaces, initial cavitation is easy to occur in advance; when the cavitation collapses, the solid particles near the cavitation are very susceptible to the impact force of the collapse and obtain acceleration, which increases the destructive force on the side wall material. Therefore, when cavitation damage and sediment wear act together, the destructive force is more severe.

[0003] In order to ensure the long-term stable and safe operation of the hydropower station and further improve the service life of the flood discharge building structure of the hydropower station, it is necessary to regularly maintain and repair the flood discharge building structure; the repair materials used should have high toughness, high wear resistance and high adhesion. In recent years, the repair mortars for the flood discharge building structure of the hydropower station are mainly divided into two categories. One is an organic polymer mortar material based on epoxy mortar, and AB type epoxy resin is often used as a bonding material to prepare the repair mortar; this type of material has the performance advantages of high toughness and high strength, but it does not have good wear resistance and is high in cost, which limits the promotion and application of this type of material. The second type is repair mortar with silicate cement as the binder. Since silicate cement is a highly brittle inorganic material, fiber materials are usually added to it to reduce its brittleness and improve the toughness of cement paste. The types of fibers added generally include polypropylene fiber, alkali-resistant basalt fiber, aluminum silicate fiber and steel fiber. However, during use, fiber-reinforced mortar has three problems: (1) Difficulty in fiber dispersion: Even if short-cut fibers with a length of only 3 mm are used, when the fibers are added to the mortar and stirred, some fibers still agglomerate, resulting in poor reinforcement effect, reduced mortar strength, and greatly The fiber content and toughening effect are limited; (2) The bonding force of organic fibers is not high: when organic fibers are used, the bonding force of the organic-inorganic interface is small and the work consumed in the fiber drawing process is small. Even after timely modification, its bonding force is still not as good as the toughening effect of inorganic fibers; (3) Inorganic fibers have high requirements for alkali corrosion resistance: most inorganic fibers can react chemically with cement hydrates and establish bonding through chemical bonds, but at the same time they require higher alkali corrosion resistance. Otherwise, within a certain period of time, the calcium hydroxide in the silicate cement will continue to react with the fibers, resulting in a reduction in the fiber diameter or even complete consumption by the reaction. Summary of the invention

[0004] The problem to be solved by the present invention is to provide a high-toughness impact-resistant and wear-resistant mortar and a preparation method and application thereof, so as to solve the problem of poor impact resistance, flexural resistance and durability of the repair mortar.

[0005] The technical solution adopted to solve the technical problem is to provide a high-toughness impact-resistant and wear-resistant mortar, comprising the following raw materials by weight: 20-30 parts of slag sulphoaluminate cement, 55-65 parts of high-strength aggregate, 5-12 parts of pre-dispersed basalt chopped fibers, 3-6 parts of water-based polyurethane emulsion, 0.05-0.1 parts of silane coupling agent and 0.02-0.08 parts of water reducing agent;

[0006] The pre-dispersed basalt chopped fibers include the following raw materials in parts by weight: 15 to 25 parts of basalt short fibers and 75 to 85 parts of granulated blast furnace slag powder.

[0007] The beneficial effects of the above technical scheme adopted in the present invention are as follows: slag sulphoaluminate cement is a low-alkali cement, and its hydration products are mainly AFt (high-sulfur calcium sulphoaluminate hydrate) and high-aluminum calcium silicate hydrate; the hydration products of slag sulphoaluminate cement do not contain calcium hydroxide, and when inorganic fibers are added for toughening, the fibers will not continue to react with alkaline oxides, thereby having good durability, and at the same time can form a strong bonding force with the cement hydration products, and through the formation of synergistic whisker toughening effect with AFt in the hydration products, the tensile and flexural strength and impact resistance of the mortar material are greatly improved; at the same time, the hydration products of slag sulphoaluminate cement contain aluminum calcium silicate hydrate, and octahedral alumina exists between the calcium silicate hydrates. Through the chemical bonds formed by alumina and calcium oxide, the strength of the calcium silicate hydrate itself is effectively enhanced, which is beneficial to improving the erosion and wear resistance of the cementitious material.

[0008] Preferably, the high-toughness impact-resistant and wear-resistant mortar comprises the following raw materials in parts by weight: 25-30 parts of slag sulphoaluminate cement, 55-61 parts of high-strength aggregate, 9-10 parts of pre-dispersed basalt chopped fibers, 4-5 parts of water-based polyurethane emulsion, 0.08-0.1 parts of silane coupling agent and 0.03-0.08 parts of water reducing agent;

[0009] The pre-dispersed basalt chopped fibers include the following raw materials in parts by weight: 20 to 25 parts of basalt short fibers and 75 to 80 parts of granulated blast furnace slag powder.

[0010] Preferably, the length of the basalt short fibers is 3 to 6 mm; and the activity index of the granulated blast furnace slag powder is greater than 95%.

[0011] Preferably, the pre-dispersed basalt chopped fibers are prepared by the following steps: mixing the basalt short fibers and granulated blast furnace slag powder and grinding them for 5 to 10 minutes.

[0012] The beneficial effects of the above technical solution adopted in the present invention are as follows: in the present invention, the basalt short fibers are pretreated, and slag is used as a dispersion medium. Under the grinding action, the fiber length can be further reduced, and the fiber exists in a disordered state in the powder, which can effectively solve the problem of poor fiber dispersion.

[0013] More preferably, the grinding medium is steel forging with a forging to material ratio of 6.0.

[0014] More preferably, the pre-dispersed basalt chopped fibers after grinding have a length of 0.1 to 1.2 mm and are in a uniformly dispersed state.

[0015] Preferably, the compressive strength of slag sulphoaluminate cement at 28 days is not less than 52.5 MPa; and the high-strength aggregate is granite with a modulus of 2.5 to 3.2.

[0016] Preferably, the aqueous polyurethane emulsion is a single-component aqueous polyurethane with a solid content greater than 35%.

[0017] The beneficial effects of the technical scheme adopted in the present invention are as follows: the one-component waterborne polyurethane added in the present invention can be evenly dispersed in the pores of cement stone, and an effective chemical bond is formed with cement hydrate through a silane coupling agent. The polyurethane polymer has good deformation ability. When the mortar is subjected to external force impact, the impact force is absorbed by its own deformation, thereby avoiding stress concentration and damage to the mortar material. Compared with other polymer toughening materials, the one-component waterborne polyurethane can form a membrane structure inside the cement stone without the addition of a curing agent, and has the performance advantages of being easy to use and highly reliable.

[0018] Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidyl ether propyltrimethoxysilane.

[0019] Preferably, the water reducer is a polycarboxylic acid water reducer or an aliphatic water reducer.

[0020] The present invention also provides a method for preparing the high-toughness impact-resistant and wear-resistant mortar, comprising the following steps:

[0021] (1) mixing slag sulphoaluminate cement, high-strength aggregate and pre-dispersed basalt chopped fibers uniformly to obtain a mixture A;

[0022] (2) adding water-based polyurethane emulsion, silane coupling agent and water reducing agent into water and mixing them evenly to obtain mixture B;

[0023] (3) Add mixture B into mixture A and stir evenly to obtain the mixture.

[0024] The present invention also provides the use of the high-toughness impact-resistant and wear-resistant mortar in preparing flood discharge building repair materials for hydropower points.

[0025] The present invention has the following beneficial effects:

[0026] (1) The high-toughness impact-resistant and wear-resistant mortar of the present invention uses slag sulphoaluminate cement as the basic cementitious material, and is matched with pre-dispersed basalt fiber and water-based polyurethane, which effectively improves the flexural strength and improves its impact performance while ensuring the compressive strength of the mortar; the prepared high-toughness impact-resistant and wear-resistant mortar has good flexural strength, compressive strength and impact resistance, and has good durability when used for repairing flood discharge buildings at hydropower points.

[0027] (2) The raw materials of the high-toughness, impact-resistant and wear-resistant mortar of the present invention are easily available, simple to prepare and low in cost, and are suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The microstructure of pre-dispersed basalt chopped fibers;

[0029] Figure 2 This is the microstructure diagram of the hydration product of slag sulphoaluminate cement. DETAILED DESCRIPTION

[0030] The features and properties of the present invention are further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The slag sulphoaluminate cement in the following examples is G·SAC52.5 slag sulphoaluminate cement produced by Tangshan Polar Bear Building Materials Co., Ltd.; the chopped basalt fiber is a product of Sichuan Errun Basalt Fiber Technology Co., Ltd.; the slag used for mixing and grinding with the chopped basalt is a product of Emeishan Hongyuan Building Materials Co., Ltd.; the water-based polyurethane emulsion is a product of Shanghai Jinlang Rubber and Plastic Technology Co., Ltd.; the silane coupling agent is a product of Qingdao Hengda New Materials Technology Co., Ltd.; and the water reducer is a product of Jiangsu Subote New Materials Co., Ltd.

[0031] Example 1

[0032] A high-toughness impact-resistant and wear-resistant mortar, comprising the following raw materials in parts by weight: 20 parts of slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, 65 parts of granite ore with a modulus of 2.5, 12 parts of pre-dispersed basalt chopped fibers, 3 parts of a single-component waterborne polyurethane with a solid content of 40%, 0.05 parts of γ-aminopropyltriethoxysilane and 0.02 parts of a polycarboxylic acid water reducer;

[0033] The pre-dispersed basalt chopped fibers include the following raw materials in parts by weight: 15 parts of basalt short fibers with a length of 6 mm and 85 parts of granulated blast furnace slag powder with an activity index of 95%.

[0034] Pre-dispersed basalt chopped fibers are prepared by the following steps:

[0035] Basalt short fibers with a length of 6 mm and granulated blast furnace slag powder with an activity index of 95% are sequentially poured into a rod mill and mixed and ground for 5 minutes; the grinding medium is steel forging, and the forging-to-material ratio is 6.0.

[0036] The high-toughness impact-resistant and wear-resistant mortar in this embodiment is prepared by the following steps:

[0037] (1) pouring slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, granite ore with a modulus of 2.5 and pre-dispersed basalt chopped fibers into a concrete mixer and stirring to obtain a mixture A;

[0038] (2) adding a single-component waterborne polyurethane having a solid content of 40%, γ-aminopropyltriethoxysilane and a polycarboxylic acid water reducer into water and mixing them evenly to obtain a mixture B;

[0039] (3) Add mixture B into mixture A and mix well. The water-cement ratio is 0.48 to obtain high-toughness, impact-resistant and wear-resistant mortar.

[0040] Example 2

[0041] A high-toughness impact-resistant and wear-resistant mortar, comprising the following raw materials in parts by weight: 25 parts of slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, 61 parts of granite ore with a modulus of 2.5, 10 parts of pre-dispersed basalt chopped fibers, 4 parts of a single-component water-based polyurethane with a solid content of 40%, 0.08 parts of γ-aminopropyltriethoxysilane and 0.03 parts of a polycarboxylic acid water reducer;

[0042] The pre-dispersed basalt chopped fibers include the following raw materials in parts by weight: 20 parts of basalt short fibers with a length of 6 mm and 80 parts of granulated blast furnace slag powder with an activity index of 95%.

[0043] Pre-dispersed basalt chopped fibers are prepared by the following steps:

[0044] Basalt short fibers with a length of 6 mm and granulated blast furnace slag powder with an activity index of 95% are sequentially poured into a rod mill and mixed and ground for 8 minutes; the grinding medium is steel forging, and the forging-to-material ratio is 6.0.

[0045] The high-toughness impact-resistant and wear-resistant mortar in this embodiment is prepared by the following steps:

[0046] (1) pouring slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, granite ore with a modulus of 2.5 and pre-dispersed basalt chopped fibers into a concrete mixer and stirring to obtain a mixture A;

[0047] (2) adding a single-component waterborne polyurethane having a solid content of 40%, γ-aminopropyltriethoxysilane and a polycarboxylic acid water reducer into water and mixing them evenly to obtain a mixture B;

[0048] (3) Add mixture B into mixture A and mix well. The water-cement ratio is 0.48 to obtain high-toughness, impact-resistant and wear-resistant mortar.

[0049] Example 3

[0050] A high-toughness impact-resistant and wear-resistant mortar, comprising the following raw materials in parts by weight: 30 parts of slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, 59 parts of granite ore with a modulus of 2.5, 5 parts of pre-dispersed basalt chopped fibers, 6 parts of a single-component waterborne polyurethane with a solid content of 40%, 0.1 parts of γ-glycidyl ether propyl trimethoxy silane and 0.04 parts of a polycarboxylate water reducer;

[0051] The pre-dispersed basalt chopped fibers include the following raw materials in parts by weight: 25 parts of basalt short fibers with a length of 3 mm and 75 parts of granulated blast furnace slag powder with an activity index of 95%.

[0052] Pre-dispersed basalt chopped fibers are prepared by the following steps:

[0053] Basalt short fibers with a length of 3 mm and granulated blast furnace slag powder with an activity index of 95% are sequentially poured into a rod mill and mixed and ground for 10 minutes; the grinding medium is steel forging, and the forging-to-material ratio is 6.0.

[0054] The high-toughness impact-resistant and wear-resistant mortar in this embodiment is prepared by the following steps:

[0055] (1) pouring slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, granite ore with a modulus of 2.5 and pre-dispersed basalt chopped fibers into a concrete mixer and stirring to obtain a mixture A;

[0056] (2) adding a single-component waterborne polyurethane having a solid content of 40%, γ-glycidyl ether propyl trimethoxy silane and a polycarboxylic acid water reducer into water and mixing them evenly to obtain a mixture B;

[0057] (3) Add mixture B into mixture A and mix well. The water-cement ratio is 0.48 to obtain high-toughness, impact-resistant and wear-resistant mortar.

[0058] Example 4

[0059] A high-toughness impact-resistant and wear-resistant mortar, comprising the following raw materials in parts by weight: 30 parts of slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, 55 parts of granite ore with a modulus of 2.5, 10 parts of pre-dispersed basalt chopped fibers, 5 parts of a single-component water-based polyurethane with a solid content of 40%, 0.1 parts of γ-glycidyl ether propyl trimethoxy silane and 0.08 parts of an aliphatic water reducer;

[0060] The pre-dispersed basalt chopped fibers include the following raw materials in parts by weight: 25 parts of basalt short fibers with a length of 3 mm and 75 parts of granulated blast furnace slag powder with an activity index of 95%.

[0061] Pre-dispersed basalt chopped fibers are prepared by the following steps:

[0062] Basalt short fibers with a length of 3 mm and granulated blast furnace slag powder with an activity index of 95% are sequentially poured into a rod mill and mixed and ground for 10 minutes; the grinding medium is steel forging, and the forging-to-material ratio is 6.0.

[0063] The high-toughness impact-resistant and wear-resistant mortar in this embodiment is prepared by the following steps:

[0064] (1) pouring slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, granite ore with a modulus of 2.5 and pre-dispersed basalt chopped fibers into a concrete mixer and stirring to obtain a mixture A;

[0065] (2) adding a single-component waterborne polyurethane having a solid content of 40%, γ-glycidyl ether propyl trimethoxy silane and an aliphatic water reducer into water and mixing them evenly to obtain a mixture B;

[0066] (3) Add mixture B into mixture A and mix well. The water-cement ratio is 0.48 to obtain high-toughness, impact-resistant and wear-resistant mortar.

[0067] Comparative Example 1

[0068] A mortar comprises the following raw materials in parts by weight: 30 parts of P.O42.5R silicate cement, 70 parts of granite ore with a modulus of 2.5 and 0.02 parts of polycarboxylate water reducer.

[0069] The mortar in this comparative example was prepared by the following steps:

[0070] Pour P.O42.5R silicate cement, granite with a modulus of 2.5, water and polycarboxylic acid water-reducing agent into a concrete mixer in sequence and mix them with a water-cement ratio of 0.42.

[0071] Comparative Example 2

[0072] A mortar comprises the following raw materials in parts by weight: 30 parts of slag sulphoaluminate cement with a compressive strength of 52.5 MPa at the age of 28 days, 70 parts of granite ore with a modulus of 2.5 and 0.02 parts of a polycarboxylate water reducer.

[0073] The mortar in this comparative example was prepared by the following steps:

[0074] Slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, granite ore with a modulus of 2.5, water and polycarboxylate water reducer are poured into a concrete mixer in sequence and stirred and mixed, with a water-cement ratio of 0.42.

[0075] Comparative Example 3

[0076] A mortar comprises the following raw materials in parts by weight: 20 parts of P.O42.5R silicate cement, 65 parts of granite ore with a modulus of 2.5, 12 parts of pre-dispersed basalt chopped fibers, 3 parts of a single-component waterborne polyurethane with a solid content of 40%, 0.05 parts of γ-aminopropyl triethoxysilane and 0.02 parts of a polycarboxylate water reducer;

[0077] The pre-dispersed basalt chopped fibers include the following raw materials in parts by weight: 15 parts of basalt short fibers with a length of 6 mm and 85 parts of granulated blast furnace slag powder with an activity index of 95%.

[0078] Pre-dispersed basalt chopped fibers are prepared by the following steps:

[0079] Basalt short fibers with a length of 6 mm and granulated blast furnace slag powder with an activity index of 95% are sequentially poured into a rod mill and mixed and ground for 5 minutes; the grinding medium is steel forging, and the forging-to-material ratio is 6.0.

[0080] The mortar in this comparative example was prepared by the following steps:

[0081] (1) Pour P.O42.5R silicate cement, granite with a modulus of 2.5 and pre-dispersed basalt chopped fibers into a concrete mixer and stir to obtain a mixture A;

[0082] (2) adding a single-component waterborne polyurethane having a solid content of 40%, γ-aminopropyltriethoxysilane and a polycarboxylic acid water reducer into water and mixing them evenly to obtain a mixture B;

[0083] (3) Add mixture B into mixture A and mix well. The water-to-binder ratio is 0.48.

[0084] Comparative Example 4

[0085] A mortar comprises the following raw materials in parts by weight: 20 parts of slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, 65 parts of granite ore with a modulus of 2.5, 12 parts of basalt short fibers, 3 parts of a single-component waterborne polyurethane with a solid content of 40%, 0.05 parts of γ-aminopropyltriethoxysilane and 0.02 parts of a polycarboxylate water reducer;

[0086] The mortar in this comparative example was prepared by the following steps:

[0087] (1) Pour slag sulphoaluminate cement with a compressive strength of 52.5 MPa at 28 days, granite with a modulus of 2.5 and basalt short fibers into a concrete mixer and stir to obtain a mixture A;

[0088] (2) adding a single-component waterborne polyurethane having a solid content of 40%, γ-aminopropyltriethoxysilane and a polycarboxylic acid water reducer into water and mixing them evenly to obtain a mixture B;

[0089] (3) Add mixture B into mixture A and mix well. The water-to-binder ratio is 0.48.

[0090] Experimental example

[0091] The mortars prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were respectively formed into compression test blocks, flexural test blocks and impact test blocks, and the test blocks were tested after curing for 28 days and 180 days under standard curing conditions, respectively. The specific testing methods were carried out in accordance with the relevant provisions of SL352-2020 "Test Procedures for Hydraulic Concrete" and CECS13:2009 "Fiber Concrete Test Method Standard", and the test results are shown in Tables 1 and 2.

[0092] Table 1 Test results of samples after curing for 28 days

[0093]

[0094]

[0095] Table 2 Test results of samples after curing for 180 days

[0096]

[0097] As shown in Table 1, using slag sulphoaluminate cement as the basic cementitious material and adding pre-dispersed basalt fiber and water-based polyurethane emulsion will not only not reduce the compressive strength of the mortar, but also effectively improve its flexural strength, greatly improving the impact resistance of the mortar material, indicating that the interface bonding of basalt fiber, water-based polyurethane and the hydration product of slag sulphoaluminate cement has a good toughening effect.

[0098] The mortar prepared with silicate cement has better compressive performance, but its compressive strength and impact resistance are lower than those of Examples 1 to 4. Even if pre-dispersed basalt fiber and water-based polyurethane emulsion are added, the flexural strength and impact resistance are improved to a certain extent after curing for 28 days, but the performance is not as good as that of Examples 1 to 4. When slag sulphoaluminate cement is added with fibers that are not pre-dispersed, the fibers are difficult to disperse evenly, resulting in weakened reinforcement, and the compressive strength, flexural strength and impact resistance are all lower than those of Examples 1 to 4.

[0099] It can be seen from Table 2 that the later strength of the high-toughness impact-resistant and wear-resistant mortar increases significantly, and the impact resistance is significantly improved. The basalt fiber pretreated by the present invention has good durability in slag sulphoaluminate cement.

[0100] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.

Claims

1. A high-toughness, impact-resistant and wear-resistant mortar, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of slag sulphoaluminate cement, 55-65 parts of high-strength aggregate, 5-12 parts of pre-dispersed basalt chopped fibers, 3-6 parts of water-based polyurethane emulsion, 0.05-0.1 parts of silane coupling agent and 0.02-0.08 parts of water reducing agent; The pre-dispersed basalt chopped fibers include the following raw materials by weight: 15-25 parts of basalt short fibers and 75-85 parts of granulated blast furnace slag powder; The length of the basalt short fibers is 3-6 mm; the activity index of the granulated blast furnace slag powder is greater than 95%; The pre-dispersed basalt chopped fibers are prepared by the following steps: Mix and grind basalt short fibers and granulated blast furnace slag powder for 5-10 minutes to obtain; The water-based polyurethane emulsion is a single-component water-based polyurethane with a solid content greater than 35%; the 28d compressive strength of the slag sulphoaluminate cement is not less than 52.5MPa; the high-strength aggregate is a granite ore with a modulus of 2.5 to 3.2; the silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidyl ether propyltrimethoxysilane; and the water reducer is a polycarboxylic acid water reducer or an aliphatic water reducer.

2. The high-toughness impact-resistant and wear-resistant mortar according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 25-30 parts of slag sulphoaluminate cement, 55-61 parts of high-strength aggregate, 9-10 parts of pre-dispersed basalt chopped fibers, 4-5 parts of water-based polyurethane emulsion, 0.08-0.1 parts of silane coupling agent and 0.03-0.08 parts of water reducing agent; The pre-dispersed basalt chopped fibers include the following raw materials in parts by weight: 20-25 parts of basalt short fibers and 75-80 parts of granulated blast furnace slag powder.

3. The method for preparing the high-toughness impact-resistant and wear-resistant mortar according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) mixing slag sulphoaluminate cement, high-strength aggregate and pre-dispersed basalt chopped fibers uniformly to obtain a mixture A; (2) adding water-based polyurethane emulsion, silane coupling agent and water reducing agent into water and mixing them evenly to obtain mixture B; (3) Add mixture B into mixture A and stir evenly to obtain the mixture.

4. Use of the high-toughness, impact-resistant and wear-resistant mortar according to any one of claims 1 to 2 in the preparation of flood discharge building repair materials for hydropower points.

Citation Information

Patent Citations

  • Basalt fiber reinforced cement based material and preparation method therefor

    CN105541209A

  • Concrete pavement repairing material and preparation method and application thereof

    CN109851304A